Scaffolding Protein Gab2 Mediates Differentiation Signaling Downstream of Fms Receptor Tyrosine Kinase - Liu, Yan (American Society for Microbiology, 2001)
Fms is the receptor for macrophage colony-stimulating factor (M-CSF) and contains intrinsic tyrosine kinase activity. Expression of exogenous Fms in a murine myeloid progenitor cell line, FDC-P1 (FD-Fms), results in M-CSF-dependent growth and macrophage differentiation. Previously, we described a 100-kDa protein that was tyrosine phosphorylated upon M-CSF stimulation of FD-Fms cells. In this report, we identify this 100-kDa protein as the recently cloned scaffolding protein Gab2, and we demonstrate that Gab2 associates with several molecules involved in M-CSF signaling, including Grb2, SHP2, the p85 subunit of phosphatidylinositol 3′-kinase, SHIP, and SHC. Tyrosine phosphorylation of Gab2 in response to M-CSF requires the kinase activity of Fms, but not that of Src. Overexpression of Gab2 in FD-Fms cells enhanced both mitogen-activated protein kinase (MAPK) activity and macrophage differentiation, but reduced proliferation, in response to M-CSF. In contrast, a mutant of Gab2 that is unable to bind SHP2 did not potentiate MAPK activity. Furthermore, overexpression of this mutant in FD-Fms cells inhibited macrophage differentiation and resulted in a concomitant increase in growth potential in response to M-CSF. These data indicate that Gab2 is involved in the activation of the MAPK pathway and that the interaction between Gab2 and SHP2 is essential for the differentiation signal triggered by M-CSF.